Mechanisms of wogonoside in the treatment of atherosclerosis based on network pharmacology, molecular docking, and experimental validation - Zhaohui Gong; Haixin Yang; Li Gao; Yi Liu; Qingmin Chu; Chuanjin Luo; Liang Kang; Huiqi Zhai; Qiang Xu; Wei Wu; Nan Li; Rong Li (BMC Complementary Medicine and Therapies)
Abstract Background Atherosclerosis serves as the fundamental pathology for a variety of cardiovascular disorders, with its pathogenesis being closely tied to the complex interplay among lipid metabolism, oxidative stress, and inflammation. Wogonoside is a natural flavonoid extracted from Scutellaria baicalensis with a variety of biological activities, including anti-inflammatory, hypolipidemic, and cardiac function improvement properties. Despite these known effects, the specific role of wogonoside in the context of atherosclerosis remains to be elucidated. Purpose To validate the efficacy of wogonoside in the treatment of atherosclerosis and to investigate its possible therapeutic mechanisms. Methods Network pharmacology was used to obtain the core targets and signaling pathways that may be efficacious in the treatment of atherosclerosis with wogonoside, which were validated using molecular docking and molecular dynamics simulations. To further validate the core targets in the signaling pathway, we performed in vivo experiments using apolipoprotein E (ApoE)-/- mice. This included pathological morphology and lipid deposition analysis of mouse aorta, serum lipid level analysis, Elisa analysis, oxidative stress analysis, reactive oxygen species (ROS) fluorescence assay, immunohistochemical analysis and protein blot analysis. Results Predictions were obtained that wogonoside treatment of atherosclerosis has 31 core targets, which are mainly focused on pathways such as Toll-like receptor (TLR) signaling pathway and NF-kappa B (NF-κB ) signaling pathway. Molecular docking and molecular dynamics simulations showed that wogonoside has good binding properties to the core targets. In vivo experimental results showed that wogonoside significantly inhibited aortic inflammatory response and lipid deposition, significantly reduced the release levels of total cholesterol (TC), triglycerides (TG), low-density-lipoprotein cholesterol (LDL-C), oxidized low density (ox-LDL) and free fatty acid (FFA), and significantly inhibited the release of inflammatory factors TNF-α, IL-1β, IL-6 and oxidative stress in ApoE-/- mice. Further molecular mechanism studies showed that wogonoside significantly inhibited the activation of TLR4/NF-κB signaling pathway in ApoE-/- mice. Conclusion Wogonoside may be an effective drug monomer for the treatment of atherosclerosis, and its mechanism of action is closely related to the inhibition of the activation of the TLR4/NF-κB signaling pathway. Graphical Abstract